Shortcomings of short hairpin RNA-based transgenic RNA interference in mouse oocytes - Sarnova, Lenka; Malik, Radek; Sedlacek, Radislav; Svoboda, Petr (Journal of negative results in biomedicine, 2010)
BACKGROUND: RNA interference (RNAi) is a powerful approach to study a gene function. Transgenic RNAi is an adaptation of this approach where suppression of a specific gene is achieved by expression of an RNA hairpin from a transgene. In somatic cells, where a long double-stranded RNA (dsRNA) longer than 30 base-pairs can induce a sequence-independent interferon response, short hairpin RNA (shRNA) expression is used to induce RNAi. In contrast, transgenic RNAi in the oocyte routinely employs a long RNA hairpin. Transgenic RNAi based on long hairpin RNA, although robust and successful, is restricted to a few cell types, where long double-stranded RNA does not induce sequence-independent responses. Transgenic RNAi in mouse oocytes based on a shRNA offers several potential advantages, including simple cloning of the transgenic vector and an ability to use the same targeting construct in any cell type. RESULTS: Here we report our experience with shRNA-based transgenic RNAi in mouse oocytes. Despite optimal starting conditions for this experiment, we experienced several setbacks, which outweigh potential benefits of the shRNA system. First, obtaining an efficient shRNA is potentially a time-consuming and expensive task. Second, we observed that our transgene, which was based on a common commercial vector, was readily silenced in transgenic animals. CONCLUSIONS: We conclude that, the long RNA hairpin-based RNAi is more reliable and cost-effective and we recommend it as a method-of-choice when a gene is studied selectively in the oocyte.
Keywords: Humans; HeLa buňky; genetické vektory; Crosses, Genetic; Mice, Transgenic; protoonkogenní proteiny c-mos; klonování DNA; Female; Transgenes; myši transgenní; Proto-Oncogene Proteins c-mos; genový knockdown; lidé; plazmidy; zvířata; myši; transgeny; Gene Knockdown Techniques; křížení genetické; Mice; oocyty; RNA, Small Interfering; malá interferující RNA; ženské pohlaví; Male; HeLa Cells; polymerázová řetězová reakce; Polymerase Chain Reaction; RNA Interference; Genetic Vectors; Animals; mužské pohlaví; Cloning, Molecular; Oocytes; Plasmids; RNA interference